Subcutaneous Connective Tissue Reaction to Methacrylate Resin–based and Zinc Oxide and Eugenol Sealers - Zmener, Osvaldo (2010)
Introduction: An evaluation was made of the connective tissue reaction in rats after subcutaneous implantation of methacrylate resin-based sealers (EndoREZ [Ultradent Products, Inc, South Jordan, UT] with a polymerization accelerator and RealSeal [Sybron Dental Specialties, Orange, CA]) and Pulp Canal Sealer (Sybron Dental Specialties), a zinc oxide and eugenol-based sealer used as the control. Methods: Silicone tubes containing the test materials were implanted in 24 Wistar rats. Solid silicone rods of the same size served as the negative controls. After 10, 30, and 90 days, the animals (n = 8 per period) were euthanized and the implants with surrounding tissues dissected and processed for routine histological evaluation. A four-category evaluation system was used to measure and record the microscopic observations according to the thickness of a fibrous capsule, the vascular changes, and the various types of inflammatory cells. Results: Initially, a severe inflammatory reaction was observed of the soft tissues in direct contact with both EndoREZ/Accelerator and Real Seal. The severity decreased over time and was resolved at the end of the experiment. Pulp Canal Sealer showed a severe tissue reaction for all observation periods. The negative controls showed an initial mild to moderate inflammatory reaction. After 30 days, healthy fibrous connective tissue was observed, which increased over time. After 10 days, no statistically significant differences between the experimental groups were observed. After 90 days, EndoREZ and RealSeal were statistically significantly less toxic than Pulp Canal Sealer (p > 0.05). Conclusions: After 90 days, both methacrylate resinbased sealers were considered biologically acceptable when implanted in subcutaneous connective tissues of the rat. Pulp Canal Sealer remained toxic for the duration of the study.